Desain Media Filter Bioring dan Karbon Blok untuk mengurangi Kesadahan Zat Kapur Air Sumur Gali: Studi Kasus Desa Pulau Tengah Kec. Menui Kepulauan Kab. Morowali Sulawesi Tengah - Usman, Usman; Rosdiana, Rosdiana; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Clean water is needed in fulfilling human needs to carry out all activities so it is necessary to know how water is said to be clean in terms of quality and can be used in adequate quantities in human daily activities. In terms of quality, there are several requirements that must be met, including physical quality consisting of odor, color, and taste, chemical quality consisting of pH, hardness, and so on as well as biological quality where the water is free from disease-causing microorganisms. One of the water sources that are still widely used by the people of Pulau Tenga Village, Kec. Menui Central Sulawesi Islands is dug well water. The high hardness value in the dug well water is 518 mg/L. It can be identified that the water contains lime so it is necessary to treat water in order to meet clean water quality standards. One of the efforts that must be done is to make water treatment by filtration. The design of the filter device is made of pipe measuring 3 inches. The filter material used for the bioring, water filter, zeolite, and activated carbon which is applied in a water filtration filter device with a filtration flow rate of 0.006 L/s.